Answer:
B
x = 3 and y = -4
Step-by-step explanation:
to solve this simultaneous equation we adopt the substitution method
we say that let
3x – 4y = 25
....................... equation 1
3x + 2y = 1........................... equation 2
from equation 2
3x + 2y = 1........................... equation 2
3x = 1-2y
divie both sides by 3
3x/3 = (1-2y)/3
x = (1-2y)/3...................................... equation 3
put x = ( 1- 2y)/3 into equation 1
3x – 4y = 25 ..................... equation 1
3( 1 -2y)/3 - 4y = 25
1-2y - 4y = 25
1 -6y =25
-6y =25 -1
-6y = 24
divide both sides by the coefficient of y which is -6
-6y/-6 = 24/-6
y = -4
put the value of y = -4 into equation 3
x = (1-2y)/3...................................... equation 3
x = ( 1- 2(-4)/ 3
x = 1 +8 /3
x = 9/3
x = 3
therefore the value of x = 3 and y = -4 respectively